Gangs, maras and other outsiders: towards an Ethnography of Latin American Gangs - Collombon, Maya (Cultura y Representaciones Sociales, 2021)
Abstract: This paper introduces, based on numerous studies, an analysis of the evolution, customs and context of Latin American gangs, which have defined their place in different urban spaces, positioning themselves through violence, and establishing different subcultures. Ethnographic research on gangs has opened the debate around the possibility of defining them through behaviors, initiation rites and their place in society, generating different questions about the current relationships with several criminal groups, as well as the stereotypes applied to their members (men and women). It seeks to reactivate the debate in the academic sphere about gangs and promote ethnographic research. The cases can be conceived as the response of some young people to a situation of rejection, in conflict with certain environment that is imposed to them as exclusive and the impossibility of finding other ways of belonging to society, obtaining a certain social prestige and economic benefits.